Comparison of immune response of the indigenous and cross bred cattle of Kerala - Francis Bastin P (Department of Animal Breeding and Genetics, College of Veterinary and Animal Sciences, 1994)
This research work aimed at comparing the immune responses of indigenous and crossbred cattle of Kerala and finding out association if any, with common diseases and also maternal immune response and the neonatal calf diseases and mortality. Thirty adult local indigenous cattle, their 36 calves, 40 adult crossbred cows and their 40 calves formed the material for the study. Primary humoral response to the test antigen, human red blood cells was assessed at zero, seven and 14th day. Secondary immune response to the test antigen was assessed on day three, seven and 14 after booster injection at 14th day. The antibody titre was assessed by direct microhaemagglutination technique. Cell mediated immune response to contact sensitizer 2,4-Dinitrochlorobenzene (DNCB) was assessed by application of two per cent solution on zero and first day followed by percutaneous challenge at the 14th day. Double fold skin thickness and area of reaction were recorded. Humoral and cell mediated immune response, the influence of genetic group, association with diseases and mortality, influence of maternal immune response on the calf immune response and association with calf diseases and mortality were assessed. The antibody titres were expressed as 1oge + 1 to make the distribution normal. Peak primary immune response was reached by day 14 (2.13) and peak secondary response was on seventh day of secondary immunization (2.98). No significant